UI/UX Design of Vendor Ordering Information System Using Design Thinking Method : Case Study CV. MOVED4 - Fauzan, Muhammad Fathan; Hanif, Isa Faqihuddin; Subarkah, Achmad Rizqon; Bagas Fadillah; Pangestu, Muhammad Bagas Adi; Fillah, Syaddad Abdurrasyid (Journal of Advances in Information and Industrial Technology, 2024)
Moved4 is an event organiser (EO) service that aims to help people across Jakarta organise events such as weddings, graduations, concerts, and seminars. They use marketing methods that are done manually, such as distributing brochures and broadcast messages. Moved4's target market is business owners aged 18-55 who need EO assistance to organise their events. The main focus in user interface (UI) and user experience (UX) design is user comfort. This is achieved through a design thinking approach consisting of four phases: empathise, define, ideate, prototype and test. MOVED4's UI/UX design received a SUS (System Convenience Scale) score of 79.25%, which indicates a high level of excellence. This indicates that users find it comfortable and easy to use the dashboard, which is crucial for successful technology adoption among target users.